The Effectiveness Visual Feedback on Postural Control Post Stroke: Literature Review - Wanda Kurnia Yuda; Umi Budi Rahayu; Rivan Danuaji (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Stroke often causes disturbances in the sensorimotor system, which can interfere with the sufferer's ability to maintain balance and movement. Visual feedback can provide real-time information regarding the position and movement of a patient's body after a stroke, by adjusting movement adjustments and controlling body posture to maintain balance. The aim of this research is to determine the effect of visual feedback from the exercises given on post-stroke patients' posture control related to muscle activity, center of pressure, balance, gait and functional ability. The method used is a literature review through searching Pubmed and Scopus articles with the keywords "Visual Feedback" AND "Postural Control" OR "Postural Instability" AND Stroke which will be identified and selected using PRISMA guidelines. The research results showed that from 488 search articles, 6 articles were obtained that met the inclusion and exclusion criteria for review, which informed that visual feedback mediated by sit to stand exercises, Dynamic Sitting Sport, Sitting Balance, or visual feedback with a stable surface and bilateral visual feedback can improve muscle activity, center of pressure, balance, gait and functional abilities of post-stroke patients. The conclusion of this research is that there is an influence of visual feedback from the exercises given on posture control in stroke patients.